CHILDHOOD LOSS AND DISHARMONY - LATER EFFECTS ON PERSONALITY AND PSYCHOPATHOLOGY - Hassanyeh, F; Eccleston, D; Williams, J (1983)
In a comparison of psychiatric inpatients and medical controls parental loss in childhood was not a differentiating factor. Psychiatric inpatients, however, had more disturbance in their home background. In the psychiatric group a disturbed childhood background was associated, on the Eysenck Personality Questionnaire, with abnormal scoring on P in both sexes, and N in males. There was, however, no specific association with psychiatric diagnosis. © 1983.